fingerprint based authentication system for exam hall - hebbaz, houssna; benabedelkader, omar (universty of elouedجامعة الوادي, 2020)
"لطالما كان تحديد الهوية والمصادقة عليها صعبًا ، ال سيما مع تطور عمليات االحتيال والتزوير والسرقة مع تقدم التكنولوجيا. في مجال التعليم ، يعتبر التحقق من هوية الطالب أمًرا رتيبًا ويستغرق وقتًا طوي ًال للمراقب والطالب ، خاصة أثناء االمتحانات. الهدف الرئيسي من هذا المشروع هو إنشاء نظام مصادقة ذكي يضمن السماح للطالب المصرح لهم فقط بالدخول إلى قاعة االمتحان دون أي تدخل بشري باستخدام ماسح بصمات األصابع قائم على االردوينو. "Identity identification and authentication has always been difficult, especially with the development of fraud, counterfeiting and theft operations with the progress of technology. In the field of education, validating the identity of the student is monotonous and time consuming for the invigilator and students, especially during exams. The main aim of this project is to create a smart authentication system which ensures that only authorized students are allowed to enter the exam hall without any human intervention using fingerprint scanner based on Arduino.
mémouer de fin master infourmatique
Keywords: ماسح بصمات األصابع ، أردوينو ، نظام ذكي ، مصادقة.; Fingerprint scanner, Arduino, smart system, Authentification.